Modeling of a Sliding Mode Controller to control the Tracking System for Solar Panels with Two Degrees of Freedom - Ali Aniss Ebrahim (Peneliti Teknologi Teknik Indonesia, 2026)
In this report, the design of a cascade Sliding Mode Controller (SMC) with a boundary layer for chattering attenuation is presented for a dual-axis solar tracking system. First, the theoretical background of this control method is presented. Then, using MATLAB/Simulink, the proposed controller is designed and simulated under various scenarios including step, sinusoidal trajectories, and external disturbances. The simulation results demonstrate high-precision tracking with a root mean square error (RMSE) of 0.15°, robust disturbance rejection, and a significant enhancement in electrical energy generation by up to 40% compared to a fixed-panel system.